A review of community-based health insurance in Nigeria - Tukur, Nura; M. B., Fatma; M. M., Fatehelrahman Elmahadi; Ismail, Suriani; Mahmud, Aidalina (Community Health Society Malaysia, 2017)
Background: The primary goal of many countries is to establish a healthcare financing system that guarantees universal health coverage (UHC) through equity in access to healthcare services as well as financial risk protection to the people. Community based health insurance (CBHI) has emerged as an alternative to reduce out-of-pocket (OOP) expenditures and improved financial risk protections in developing countries like Nigeria. The aim of this study is to review the CBHI in Nigeria and highlight the issues, weaknesses and strengths of the system. Materials and Methods: A systematic literature review on the CBHI was conducted using relevant studies searched from electronic databases: MEDLINE, Pubmed, scienceDirect.com, PLOS and public search engine (Google). It was done on 16th January, 2017. The phrases used are ‘health financing’, ‘community health insurance’ in ‘Nigeria’ which were put together by Boolean operator “and” articles or reports. Relevant materials for the past 7 years were included. A total of 5 articles fulfilled the criteria for review. SWOT (strength, weakness, opportunity and threat) tool was used for the analysis. Result: The strengths of CBHI scheme in Nigeria are it reduces OOP health expenditure and improves utilization rate on healthcare. However, the weaknesses are that the scheme tends to cover a comparatively small proportion of the social class, namely the lower social class. Also, involvement of the community sometimes is ineffective due to inadequate funding. The opportunities are that the CBHI scheme increases efforts towards improving healthcare system in the country and enables equity in access to healthcare. The threats are weak policy, lack of political commitment to health, poor funding especially in primary healthcare and poverty. Conclusion: Nigeria must start to make more commitment to health care, if they want to achieve UHC. The rate of out of pockets health expenditure is still very high and catastrophic on Nigerian healthcare system. Recommended strategies needs to be addressed urgently in order to improve equity in access to health care service as well as effective financial risk protection. CBHI may not be suitable in all situations but can play an important role in to health care programs in Nigeria.